2013
DOI: 10.1080/10408398.2012.706661
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Attributes of Cereals by Germination and Fermentation: A Review

Abstract: The nutritional quality of cereals and the sensorial properties of their products are sometimes inferior as compared to other sources of food which is due to the lower protein content and starch availability, the presence of determined antinutrients (phytic acid, tannins, and polyphenols) and the coarse nature of the grains. To ameliorate the nutritional qualities of cereals, they are processed in a number of ways. This review summarizes the enhancement in the nutritional value as well as the functional charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(118 citation statements)
references
References 150 publications
7
100
0
11
Order By: Relevance
“…The increases observed of TPC during germination can be explained by the action of endogenous esterases synthesized during germination which can lead to the release of cell wall bound phenolic compounds. Also, the biochemical reactions in germinating grain could lead to the synthesis of new phenolic compounds [7]. Fermentation process carried out with different microorganism starters increased similarly TPC levels by about 55 % respect to raw seeds, whilst no significant differences (p > 0.05) between the treatments were observed (Fig.…”
Section: Effect Of Processing On Total Phenolic Compoundsmentioning
confidence: 96%
See 1 more Smart Citation
“…The increases observed of TPC during germination can be explained by the action of endogenous esterases synthesized during germination which can lead to the release of cell wall bound phenolic compounds. Also, the biochemical reactions in germinating grain could lead to the synthesis of new phenolic compounds [7]. Fermentation process carried out with different microorganism starters increased similarly TPC levels by about 55 % respect to raw seeds, whilst no significant differences (p > 0.05) between the treatments were observed (Fig.…”
Section: Effect Of Processing On Total Phenolic Compoundsmentioning
confidence: 96%
“…In this sense, the fermentation and/or germination are viewed as desirable methods for grain processing because of its low cost, low energy requirements, with acceptable and diversified flavours for human consumption [7]. In addition, research has shown that germination and fermentation can not only improve nutritional quality and functional properties of several grains but also reduce the anti-nutritional factors [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is understood that maize, among the used grains in the study, has the highest content of ferulic acid in all fractions. Ferulic acid at the highest level in wheat bran is a structural element of cell wall polysaccharides and most of them are covalently bound with the structures of the cell wall (Singh et al 2013). It is stated that the quantity of free ferulic acid in grains is 0.1-0.5%, most of it bound with polysaccharides and sterols (Zhao & Moghadasian 2008).…”
Section: Contents Of Ferulic Acid In Grainsmentioning
confidence: 99%
“…The free ferulic acid quantity in grains is low but during the processes of fermentation, germination, and cooking, it turns from the bound form into the free form, being healthier (Singh et al 2013). While it is stated that germination in grains will affect ferulic acids differently, the germination process will also change the contents of ferulic acid (Hübner & Arendt 2013).…”
Section: Effect Of Fermentation Germination and Grindingmentioning
confidence: 99%
“…It is often consumed as a fresh or canned vegetable and is widely consumed globally 10 . Researchers have investigated the potential of germinating kernels, and using these as sprouts, to enhance the nutritional value of the material as well as providing a novel food product for consumers 11 . However, few reports evaluate the effect of germination on the nutritional quality of sweet corn, and the role of gene expression in manipulating germination and the production of nutrients.…”
Section: Introductionmentioning
confidence: 99%